PENGARUH METODE PEMBELAJARAN DEMONSTRASI BERBANTUAN SOFTWARE GEOGEBRA TERHADAP PEMAHAMAN MATEMATIKA SISWA PADA POKOK BAHASAN TRANSFORMASI GEOMETRI - Lilis Rodiawati (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2016)
This research aim to to analyze the influence of study method demonstrate by software geogebra to understanding of student mathematics. Research method used in this research is experimen by desain is research of One Short Chase Study. To get the research data used by instrument of tes essay of mathematics and response enquette to method demonstrate the. this Research population is alk student class X, with the class A as sampel research amount to 40 student. Result of research indicate that the mean assess the understanding of student mathematics of equal to 35. analysis of Data of enquette of respon student to study method demonstrate by software geogebra show 85% giving positive response. And test the influence show the happening of influence of applying of study method demonstrate by software geogebra to understanding of student mathematics.Â Keyword: method demonstrate, geogebra, mathematics